Introducción al Ecomunitarismo y a la educación ambiental Una lectura chilena de la obra de Sirio López Velasco - Salas, Ricardo; de la Fuente, José (Ariadna Ediciones, 2021)
The ecommunitarian plural tendency, an indispensable guide for a new historical sense, shares A. Lincoln's definition of democracy: "government of the people, by the people and for the people", where intercultural experiences constitute the fertile ground for exchanging Good Living , regulated by an Environmental Education as a process of awareness composed of the "critical unveiling of the oppressions and devastations that we live-witness and the transforming-overcoming action of the same". Indeed, one of the purposes is to transform society in an ecommunitarian sense at all levels, from the local to the planetary, preparing the qualitative change that will open the doors of a large-scale transition to replace capitalism with a dignified, decent, values, aesthetics, ethics, practice, science and participation. This education excludes machismo and homophobia, and includes respect for health and sexual education from puberty to adulthood.